Adherence to Direct Observed Treatment Short-Course Treatment in Tuberculosis: Application of the Health Belief Model - Pusporini; Didik Gunawan Tamtomo; Hanung Prasetya (Journal of Health Promotion and Behavior, 2024)
Background: Tuberculosis (TB) is a disease that is a public health priority, because it was the leading infectious disease killer before COVID-19 which caused more than 1.4 million deaths in 2019. Non-compliance of TB patients to undergo regular treatment can be an obstacle in achieving a cure rate. and high treatment success. This study aimed to analyze the effect of the Health Belief Model application on Direct Observed Treatment Short-Course (DOTS) treatment adherence for Tuberculosis in Karanganyar Regency. Subjects and Method: Cross-sectional study was conducted in Karanganyar, Central Java, Indonesia. The study population was Tuberculosis patients undergoing Direct Observed Short-Course Treatment. A total of 200 Tuberculosis Patients undergoing DOTS was selected using purposive sampling. The dependent variable was DOTS compliance. The independent variable was construct of health belief model. Data were collected using a questionnaire and analyzed using a multiple logistic regression. Results: Perceived threat (b= 0.20; 95% CI= 0.06 to 0.35; p= 0.007), perceived benefit (b= 0.31; 95% CI= 0.14 – 0.49; p= 0.001), and self-efficacy (b= 0.24; 95% CI= 0.13 to 0.36; p< 0.001) significantly increased TB-DOTS compliance. Perceived barrier significantly decreased TB-DOTS compliance (b= -0.21; 95% CI= -0.31 to -0.11; p< 0.001). Conclusion: Perceived threat, perceived benefit, and self-efficacy significantly increase TB-DOTS compliance. Perceived barrier significantly decreases TB-DOTS compliance.